2016
DOI: 10.1016/j.pbb.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The GLP-1 agonist exendin-4 attenuates self-administration of sweetened fat on fixed and progressive ratio schedules of reinforcement in rats

Abstract: GLP-1 agonists such as exendin-4 (EX4) are used in the treatment of type 2 diabetes and have the additional benefit of promoting weight loss. GLP-1 agonists decrease feeding through peripheral affects, but recent evidence suggests they may also influence sweet or high fat preference, as well as the motivation to obtain these tastants. Yet it remains unclear how GLP-1 induced alterations in food preference influences the decrease in overall feeding. The current study sought to determine if EX4 affects the reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…However, it is important to note that we also observed substantial individual variation in the latency to nosepoke and first IC rewarded at the 2.4 g/kg dose. This is similar to results in our previous study in which 2.4 g/kg EX4 increased the latency to the first lever press in a model of sweetened fat self-administration (Bernosky-Smith et al, 2016). Such individual differences should be explored further in future studies of EX4 on motivation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, it is important to note that we also observed substantial individual variation in the latency to nosepoke and first IC rewarded at the 2.4 g/kg dose. This is similar to results in our previous study in which 2.4 g/kg EX4 increased the latency to the first lever press in a model of sweetened fat self-administration (Bernosky-Smith et al, 2016). Such individual differences should be explored further in future studies of EX4 on motivation.…”
Section: Discussionsupporting
confidence: 89%
“…Specific to nausea, we have previously reported that EX4 did not induce pica in a kaolin test at any of these doses (Bernosky-Smith et al, 2016). It is possible that the IC task is more sensitive to visceral malaise than the kaolin test, and therefore the decrease in IC responding, particularly at higher doses of EX4 could have a nausea component.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As opposed to ghrelin, GLP-1 signaling reduces instrumental responding for high fat/sucrose food rewards. Administration of exendin-4 in rats, for example, whether via ip injection [ 66 , 83 , 84 ] or icv infusion [ 66 , 85 ], dampens motivated lever pressing for sucrose. As a primary CNS node in the gut-to-brain axis, it is not surprising that the NTS contributes to the central effects of GLP-1 signaling on food motivated behaviors.…”
Section: Food Motivationmentioning
confidence: 99%